SIRT1 and SIRT7 expression in adipose tissues of obese and normal-weight individuals is regulated by microRNAs but not by methylation status - Kurylowicz, A; Owczarz, M; Polosak, J; Jonas, M I; Lisik, W; Jonas, M; Chmura, A; Puzianowska-Kuznicka, M (International Journal of Obesity, 2016)
Background/Objective: Given their importance in the regulation of metabolism, sirtuins (SIRTs) constitute promising subjects of research on the pathogenesis of obesity and the metabolic syndrome. The aim of this study was to assess whether obesity in humans is associated with changes in the expression of SIRT genes in adipose tissue and whether epigenetic mechanisms, DNA methylation and microRNA (miRNA) interference, mediate in this phenomenon. Subjects/Methods: The expression of SIRTs and of SIRT1 and SIRT7 mRNA-interacting miRNAs was evaluated by real-time PCR in visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) of 58 obese (body mass index (BMI) >40 kg m −2 ) and 31 normal-weight (BMI 20–24.9 kg m −2 ) individuals. The methylation status of SIRTs was studied by the methylation-sensitive digestion/real-time PCR method. Results: SIRT1 mRNA levels were lower in adipose tissues of obese patients than of normal-weight controls (VAT: P =0.0002, SAT: P =0.008). In contrast, expression of SIRT7 was higher in adipose tissues of obese patients than in the control group (VAT: P =0.001, SAT: P =0.008). The mean methylation of the SIRT1 and SIRT7 CpG islands was similar in tissues with high and low expression of these genes, and there was no correlation between the level of expression and the level of methylation. On the other hand, expression of SIRT1 in VAT of obese subjects correlated negatively with the expression of miR-22-3p ( P <0.0001, r s =−0.514), miR-34a-5p ( P =0.01, r s =−0.326) and miR-181a-3p ( P <0.0001, r s =−0.536). In turn, expression of SIRT7 in VAT of slim individuals correlated negatively with the expression of miR-125a-5p ( P =0.003, r s =−0.562) and miR-125b-5p ( P =0.018, r s =−0.460). Conclusions: We observed obesity-associated downregulation of SIRT1 and upregulation of SIRT7 mRNA levels that were not associated with the methylation status of their promoters. We found a negative correlation between mRNA levels of SIRT1 in VAT of obese individuals and SIRT7 in VAT of the normal-weight subjects and expression of the relevant miRNAs.